2020
DOI: 10.1016/j.clnu.2020.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for the management of home parenteral nutrition during the SARS-CoV-2 pandemic: A position paper from the Home Artificial Nutrition and Chronic Intestinal Failure Special Interest Group of ESPEN

Abstract: The management of patients with chronic intestinal failure requiring home parenteral nutrition has been and will continue to be impaired during the SARS-CoV-2 pandemic. Multidisciplinary intestinal failure teams may have to adapt their clinical approaches to home care, outpatient care as well as hospital admission and discharge in order to keep this vulnerable group of patients as safe and well as possible during the unprecedented challenges that countries are facing during the pandemic. Equally, it is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Prevention of infection with COVID‐19 is thought to be reduced through mask usage 11 given the risk of airborne viral infections, 12 and masks should therefore be available for all carers, whether home care nurses or relatives. The ready availability of monitoring through biochemical assessments, clinic appointments, pertinent radiological investigations, and access to fully staffed teams are important strategies to protect these vulnerable patients, as recommended by the European Society for Clinical Nutrition and Metabolism (ESPEN) 6,13,14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention of infection with COVID‐19 is thought to be reduced through mask usage 11 given the risk of airborne viral infections, 12 and masks should therefore be available for all carers, whether home care nurses or relatives. The ready availability of monitoring through biochemical assessments, clinic appointments, pertinent radiological investigations, and access to fully staffed teams are important strategies to protect these vulnerable patients, as recommended by the European Society for Clinical Nutrition and Metabolism (ESPEN) 6,13,14 …”
Section: Introductionmentioning
confidence: 99%
“…The ready availability of monitoring through biochemical assessments, clinic appointments, pertinent radiological investigations, and access to fully staffed teams are important strategies to protect these vulnerable patients, as recommended by the European Society for Clinical Nutrition and Metabolism (ESPEN). 6,13,14 Patients with IF share similar key characteristics with patients who are most at risk for COVID-19. As a population, they are at risk of malnutrition and have comorbidities and, as a population, are getting older: 20%-36% of patients receiving HPN were aged >65-69 years, 10 with ≤20% having multiple comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen articles comprising guidelines, consensus, recommendation, and position papers were excluded from the ranking process. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] An average of 27 articles (range: 15-53) of the 152 from the primary literature were denoted as most important by individual members of the author group. Five papers from the primary literature were collectively identified (receiving 5 or more votes) as most important by the authors.…”
Section: Resultsmentioning
confidence: 99%
“…UK study showed that remote solutions can be safely introduced in HPN. Considering the rapid growth of the number of HPN patients it can help with the demand of trained medical staff reducing the need for hospital attendance of patients, traveled miles to maximize the high satisfaction from medical care [17] . Other studies confirm that telehealth may be effective and cost-saving [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…ESPEN recommends self-isolation of HPN patients, protective equipment during visits, the introduction of telemedicine, avoiding face-to-face consultations and limiting blood testing to necessary ones. The need for established strategies for patients’ discharge from the hospital and transfer to the IF unit is underlined [ 17 , 18 ]. Those recommendations are similar to the position paper proposed by the Polish expert group concerning principles of home nutrition during a pandemic [19] .…”
Section: Introductionmentioning
confidence: 99%